Geospatial data infrastructure: concepts and applications - A. Kadir, Abd. Majid; Desa, Ghazali; Omar, Abdullah Hisam (2004)

(untitled)
GIS is a computer system capable of assembling, storing, manipulating, and displaying geographically reference information. Practitioners often refer to the “total GIS” as including operating personnel and the data that go into the system.